Improving students' mathematical representation ability through problem-based learning model - Safrita, Helfi; Siregar, Syarifah Nur; Murni, Atma (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
The basis of the problem in this research is the low level of mathematical representation ability among students in class IX B at SMP IT Al Fityah Pekanbaru. The initial test results showed that the percentage of students achieving the maximum score in the visual representation indicator was 32%, in the mathematical expression representation indicator was 43%, and in the word representation indicator was 36%. This study was conducted in two cycles using the problem-based learning model on the topic of geometric transformation. Each cycle included planning, action, observation, and reflection activities. The purpose of this study was to improve the learning process and enhance students' mathematical representation abilities. Data were collected using observation techniques and mathematical representation ability tests. The results showed improvements in both the learning process and students' abilities. The average percentage of students achieving the maximum score across the two cycles was 86% in visual representation, 82% in mathematical expression representation, and 52% in word representation. It can be concluded that the problem-based learning model is an effective teaching method for improving students' mathematical representation abilities.